Spider silk inspired bead-like aramid nanofibers via hydrogen-bond donor strategy for synergistic reinforcement of high-performance rubber composite. (15th April 2023) - Xu, Minghan; Zhang, Keyu; Wang, Lu; Wang, Qingfu
Abstract: Aramid nanofibers (ANFs) are of significant scientific interest in various scientific and industrial fields. However, a big problem encountered in the application of ANFs is the agglomeration and the very inert surface. Herein, inspired by the shiny water droplets on a spider's web, we report a novel, green and effective method to fabricate bead-like ANFs with homogeneous knots via a hydrogen-bond donor strategy. It is revealed that γ-aminopropyl triethoxysilane is not only effective in constructing multiple hydrogen bonding interactions with the amide groups of ANFs, but also can induce the self-assembly of the interfacial polycondensation of ethyl silicate to fabricate a spindle-knots structure. The knots are rich in silanol and amino groups being able to establish covalent bonds between ANFs and polymer matrix and improve the filler dispersion in a silica hybrid system. Therefore, the bead-like ANFs synergistically reinforce the silica filled polymer composites by significantly enhancing vulcanization rate, tensile strength, elongation at break, abrasion resistance, as well as the dynamic mechanical properties. The process does not rely on any toxic and corrosive agents and the bioinspired strategy offers new insights into the design of functional aramid nanofibers and the potential application in rubber industry. Highlights: Spider Silk inspired bead-like aramid nanofibers are fabricated by hydrogen-bond donor strategy. The hydrogen-bond donor can induce self-assembly of the interfacial polycondensation of SiO2 nanoparticles. The knots with silanol and amino groups are able to further establish covalent bonds between ANFs and polymer matrix. The bead-like ANFs synergistically reinforce the silica filled polymer composites.